Cryocoolers 11 2002
DOI: 10.1007/0-306-47112-4_47
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of DC Gas Flows in a Double-Inlet Pulse Tube Refrigerator with a Second Orifice Valve

Abstract: We have observed the secondary flow induced in a double-inlet pulse tube refrigerator by using a smoke-wire flow visualization method and investigated the effects of the opening of the bypass valve on the flow behavior of the secondary flow, especially of the DC flow. Also, the effect of a second orifice valve on the secondary flow has been visually investigated. Based on the observations, the relationship between the cooling performance and the dynamic behavior of the secondary flow has been determined. It ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Experimental condition suitable for smoke-wire visualization was determined based on the results of the preliminary and previous experiments using the pulse tube refrigerator with the valve configuration [10]. The frequency of the gas oscillation was 6 Hz, and the amplitude of the pressure wave defined as the compression ratio between the high and low pressures at the inlet of the regenerator was 1.2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental condition suitable for smoke-wire visualization was determined based on the results of the preliminary and previous experiments using the pulse tube refrigerator with the valve configuration [10]. The frequency of the gas oscillation was 6 Hz, and the amplitude of the pressure wave defined as the compression ratio between the high and low pressures at the inlet of the regenerator was 1.2.…”
Section: Methodsmentioning
confidence: 99%
“…The cause of this difference in the velocities near the wall can be attributed to whether the DC gas flow exists or not. For the double-inlet refrigerator, it was already reported that the DC gas flow is induced and the overall secondary flow is formed as a superposition of the DC gas flow on the acoustic streaming, and that under the optimized opening of the bypass valve, the velocity of the overall secondary flow decreases to almost zero in the core region while it increases near the wall [10]. In the case of the diaphragm D50 refrigerator, the DC gas flow is not induced owing to the diaphragm unit and accordingly the secondary flow only results from the acoustic streaming so that the velocity of the secondary flow near the wall decreases as a result of a decrease of the velocity in the core region.…”
Section: Visual Observation Of Oscillating Flowmentioning
confidence: 99%
“…The resistance for air flow along the direction indicated by the arrow was larger than that along the opposite direction, although the difference was less than 12% under the experimental conditions used here [10]. The effect of valve configuration on the flow behavior of the secondary flow, on the cooling performance, and on the pressure-volume (P-V work) diagram for gas was investigated.…”
Section: Introductionmentioning
confidence: 93%
“…Acoustic streaming is an axisymmetric convection in the pulse tube where the fluid flows toward the cold end in the core region and the associated return flow goes toward the hot end along the peripheral wall [10]. In general, the larger the temperature difference, the better the performance.…”
Section: Performance Of Double-valve Configurationmentioning
confidence: 99%
See 1 more Smart Citation